PERBANDINGAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN COCOK BEBEK (Kalanchoe pinnata) DENGAN METODE DPPH DAN ABTS - Boima Situmeang; Weny JA Musa; Nurhayati Bialangi; Nani Yulianti (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
Kalanchoe pinnata leaves are known as a medicinal plant containing secondary metabolites with potential antioxidant activity. This study aimed to compare the antioxidant activity of the ethanol extract of Kalanchoe pinnata leaves using DPPH and ABTS methods. Extraction was carried out by maceration using ethanol as a solvent from 50 g of dried leaf simplicia, yielding 7.2 g of thick extract with a yield of 14.4%. Antioxidant activity was evaluated at concentrations of 20, 40, 60, 80, and 100 ppm. The results showed that the percentage of inhibition increased with increasing extract concentration in both methods. In the DPPH method, the highest inhibition value was 51.1605% at 100 ppm, while in the ABTS method it was 47.7203%. The IC₅₀ values obtained were 93.54 ppm for the DPPH method and 103.01 ppm for the ABTS method. Based on these values, the antioxidant activity of the ethanol extract of Kalanchoe pinnata leaves was categorized as strong in the DPPH method and moderate in the ABTS method. In conclusion, the DPPH method showed higher antioxidant activity compared to the ABTS method. The ethanol extract of Kalanchoe pinnata leaves has the potential to be developed as a natural antioxidant source in pharmaceutical and functional food applications.